PEMBERDAYAAN EKONOMI BASIS ZAKAT PRODUKTIF MELALUI PROGRAM KAMPUNG TERNAK KAMBING BAZNAS GRESIK TERHADAP MUSTAHIK - Salsabilla Salsabilla; Wage Pramita Ratnasari (Jurnal Kommunity Online, 2020)
AbstractThe problem of poverty is a challenge for the frontline in Indonesia, including in Kertosono Village, Gresik Regency, East Java. Kertosono Village is a village with a high level of poverty. This can be seen from the many village people who work as farm laborers and fishpond laborers. Baznas Gresik as a zakat collection and management agency established by the government seeks to alleviate the Gresik community from poverty. Now the distribution of zakat is carried out productively, meaning that zakat is given to beneficiaries or mustahiks to finance productive activities such as providing working capital or initial capital assistance. One of the programs is the Productive Goat Livestock Village which is held in the village of Kertosono Sidayu Gresik. This research aims to determine the process and results of the economic empowerment program of the Productive Goat Livestock Village of Baznas Gresik. This research uses qualitative research methods through interviews, observation and documentation. The results of this study indicate that there are five processes in economic empowerment as well as several program results that have an influence on improving the economy of the mustahik family. The Productive Goat Livestock Village Program is considered successful in the economic empowerment program it has implemented for the last five years, namely 2015 - 2020.Keywords: economic empowerment; mustahik; productive zakatAbstrakPersoalan kemiskinan menjadi tantangan garda terdepan di Indonesia, termasuk di Desa Kertosono kabupaten Gresik, Jawa Timur. Desa Kertosono merupakan desa dengan tingkat kemiskinan yang tinggi hal ini dapat dilihat dari banyaknya masyarakat desa yang bekerja sebagai buruh tani dan buruh tambak. Baznas Gresik sebagai lembaga pengumpulan dan pengelolaan zakat yang dibentuk oleh pemerintah berupaya untuk mengentaskan masyarakat Gresik dari kemiskinan. Kini pendistribusian zakat dilakukan secara produktif artinya zakat diberikan kepada penerima manfaat atau mustahik untuk membiayai kegiatan produktif seperti pemberian modal kerja atau bantuan modal awal. Salah satu programnya adalah Kampung Ternak Kambing Produktif yang diselenggarakan di desa Kertosono Sidayu Gresik.jpenelitian ini bertujuan untuk mengetahui proses dan hasil dari program pemberdayaan ekonomi Kampung Ternak Kambing Produktif Baznas Gresik. Penelitian ini menggunakan metode penelitian kualitatif melalui wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini menunjukkan bahwa ada lima proses dalam pemberdayaan ekonomi serta beberapa hasil program yang memiliki pengaruh dalam peningkatan ekonomi keluarga mustahik. Program Kampung Ternak Kambing Produktif ini dinilai berhasil dalam program pemberdayaan ekonomi yang dilaksanakannya selama lima tahun terakhir yakni tahun 2015 – 2020.Kata kunci: pemberdayaan ekonomi; mustahik; zakat produktif